Endoscopic Treatment of Sphenoid Sinus Mucocele: Case Report and Surgical Considerations - Joel Caballero García; Adolfo Michel Giol Álvarez; Iosmill Morales Pérez; Nélido Gonzales Gonzales; Adolfo Hidalgo Gonzáles; Peggys Oleidis Cruz Perez (Case Reports in Otolaryngology)
Introduction. The paranasal sinuses mucoceles are benign expansive cystic lesions that occur rarely in the sphenoid sinus and contain mucous material enclosed by cylindrical pseudostratified epithelium. Objective. To report one case of sphenoid sinus mucocele that occurred with headache and was submitted to surgical treatment through endonasal endoscopy approach. Case Report. 59-year-old male patient with history of increasing frontoorbital, bilateral, fluctuating headache and exophthalmos. There was no other associated clinical abnormality. Computed Tomography (CT) and Magnetic Resonance Image (MRI) scans confirmed an expansive mass of sphenoid sinus, suggesting mucocele. The patient was submitted to endonasal endoscopic surgery with posterior ethmoidotomy, large sphenoidotomy, and marsupialization of the lesion. Conclusion. Mucoceles of the sphenoid sinus are a very rare condition with variable clinical and radiological presentation. Surgical treatment is absolutely indicated and early treatment avoids visual damage that can be permanent. Endonasal endoscopic approach with drainage and marsupialization of sphenoid sinus, using a transnasal corridor, is a safe and effective treatment modality.